2019
DOI: 10.1155/2019/7624253
|View full text |Cite
|
Sign up to set email alerts
|

Testing Bioimpedance to Estimate Body Fat Percentage across Different Hip and Waist Circumferences

Abstract: Many studies have validated the use of bioimpedance analysis (BIA) to quantify body fat percentage (BF%). However, it is unknown if some model types (i.e., hand to hand, foot to foot, and hand to foot) are differing in their validity depending on hip and waist circumferences. The purpose of this study was to compare the difference in BF% between three BIA models (i.e., hand to hand, foot to foot, and hand to foot) against the Bod Pod across different hip and waist circumferences. A total of 92 people aged 19-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Long et al. compared three types of BIA devices (hand‐to‐hand, hand‐to‐foot, foot‐to‐foot electrodes) to a Bod Pod and found that BIA estimates of BF were lower compared to BodPod only among participants in the highest tertile for WC (104.6 ± 8.7 cm) 43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long et al. compared three types of BIA devices (hand‐to‐hand, hand‐to‐foot, foot‐to‐foot electrodes) to a Bod Pod and found that BIA estimates of BF were lower compared to BodPod only among participants in the highest tertile for WC (104.6 ± 8.7 cm) 43 …”
Section: Discussionmentioning
confidence: 99%
“…These findings are substantiated by another study that also investigated the effects of a high WC on BIA estimates. Long et al compared three types of BIA devices (hand-to-hand, hand-to-foot, foot-to-foot electrodes) to a Bod Pod and found that BIA estimates of BF were lower compared to BodPod only among participants in the highest tertile for WC (104.6 � 8.7 cm) 43. Weight loss and the resulting reduction in WC would be ex-pected to reduce the abdomen to thigh contact and improve the accuracy of body composition estimates in the seated position.…”
mentioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) is a non-invasive, low-cost, helpful, and validated tool for estimating body composition 48 . The analysis is achieved by measuring the bioimpedance of an electrical current transmitted to the body through electrodes placed on the feet 49 . On the day of the study, a body composition analyzer, which employed BIA, was used to estimate body composition (BC-533 InnerScan Body Composition Monitor ® , Tanita Corp., Itabashi-Ku Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) is a non-invasive, low-cost, useful, and validated tool for estimating body composition 33 . The analysis is achieved by measuring the bioimpedance of an electrical current transmitted to the body through electrodes placed on the feet 34 . On the day of the study, a body composition analyzer, which employed BIA, was used to estimate body composition (BC-533 InnerScan Body Composition Monitor®, Tanita Corp., Itabashi-Ku Tokyo, Japan).…”
Section: Body Composition Estimationmentioning
confidence: 99%